Morphological ontogeny of Ctenobelba brevipilosa (Acari: Oribatida: Ctenobelbidae) - Seniczak, Stanisław; Ivan, Otilia; Marquardt, Tomasz; Seniczak, Anna (Zootaxa, 2020)
The morphological ontogeny of Ctenobelba brevipilosa Mahunka, 1964 is described and illustrated for the first time; this species was investigated since its description mainly in ecological aspect. The adult instar is of medium size, with setiform bothridial seta, bearing 11–17 anterior branches, and with short notogastral setae. Seta d is absent from genua I–III and all tibia. The bothridial seta of juveniles is setiform and barbed, and prodorsal and gastronotal setae are short, except of medium sized ro. Nymphs are quadrideficient and eupheredermous, i.e. they carry the exuvial scalps of previous instars. Anal valves of protonymph and deutonymph have two pairs of alveolar setae, which is rare in Brachypylina. In the juvenile instars, seta d on all genua and tibiae is present.